The politics of precaution: Genetically modified crops in developing countries - Paarlberg, Robert L. (International Food Policy Research Institute, 2001)
In this original study Robert Paarlberg examines local policy responses to GM crop technologies in four important developing countries: Brazil, India, Kenya, and China.